THE MOLECULAR MECHANISMS OF SELECTED PATHOLOGICAL PROCESSES IN THE CELL - Modriansky, Martin (Biomedical papers, 2010)
Dear Readers,I would like to present conference abstracts of 14 student scientific talks. The conference is a part of a project 305/09/H048 from the Grant Agency of the Czech Republic entitled "Molecular mechanisms of selected pathological processesin the cell". It is a project joining 19 doctoral students who come from the Faculty of Medicine and Dentistry,Palacky University in Olomouc and Institute of Biophysics in Brno. The students conduct their doctoral studies infive fields of biomedical research: medical biology, medical biophysics, biochemistry, pharmacology and pathology.The primary goal of the project is to support the individual endeavors of the students and facilitate the building ofinterdepartmental teams. The entire team, of students and their supervisors, meets annually to present results andshare research experience in a short two-day conference. Each participant gives an oral presentation of his/her results.These are then presented as abstracts.Martin Modriansky
Keywords: ...